Analisis Pengaruh Tutupan Lahan terhadap Distribusi Suhu Permukaan: Kajian Urban Heat Island di Jakarta, Bandung dan Surabaya - Muzaky, Handis; Jaelani, Lalu Muhamad (Jurnal Penginderaan Jauh Indonesia, 2019)
In 2015, more than half of Indonesia's population lived in urban areas that caused the growth of impervious surface area. The impervious surface is high heat-absorbance. Thus, the air temperature in this area is higher compared to the surrounding area. This phenomenon is known as Urban Heat Island (UHI). To examine the impact of UHI, continuous temperature monitoring is needed. Temperature monitoring using weather stations has limitations in terms of coverage area, then remote sensing methods could be useful to obtain data with sufficient spatial distribution. This study examines UHI phenomena in three densest cities in Indonesia (Jakarta, Bandung, and Surabaya) using Landsat 8 OLI/TIRS imagery. Estimation of Land Surface Temperature (LST) using the Single Channel (SC) algorithm and land cover identification using three spectral indices: Vegetation Difference Index (NDVI), Modified Normalized Difference Water Index (MNDWI), and Visible Red Near Infrared Build-Up Index (VrNIR-BI). The average surface temperature in Jakarta, Bandung, and Surabaya were 35.21°C, 28.52°C, and 31.69°C respectively. The relationship between LST and land cover was analyzed using Pearson product-moment correlation. The correlation value between LST and NDVI in Jakarta, Bandung, and Surabaya were -0.49; -0,51; and -0.49 while between LST and VrNIR-BI were 0.49; 0.51; and 0.48.